Critical Planetary Romanticism: Ecology, Evolution, and Erotic Thinking Ecology, Evolution, and Erotic Thinking - Bauman, Whitney (Journal for the study of religion, nature and culture, 2021)
Queer Theory (QT) has expanded since the 1990s beyond critiques of normative understandings of gender and sex, to a broader critique of normative thinking in general. The destabilizing force of QT has been utilized to critique understandings of "nature", highlighting how nature is a historically constructed and changing category. This article puts queer theorists into dialogue with "critically romantic" scientists of the nineteenth and early twentieth centuries. Though not often thought of as "queer" critically romantic scientists such as Ernst Haeckel understood that "nature", from an ecological and evolutionary standpoint, was an unstable category. Using these earlier thinkers in dialogue with QT, I bring queer thinking back to nature in an erotics of thought, or what I call a critical planetary romanticism (CPR). A CPR opens us on to the evolving and entangled planetary community and the co-construction of the planetary grounds of our own thought.